CTNI-67. DUAL INHIBITION OF POST-RADIOGENIC ANGIO-VASCULOGENESIS BY OLAPTESED PEGOL (NOX-A12) AND BEVACIZUMAB IN GLIOBLASTOMA – INTERIM DATA FROM THE FIRST EXPANSION ARM OF THE GERMAN PHASE 1/2 GLORIA TRIAL. (14th November 2022) - Giordano, Frank; Layer, Julian; Leonardelli, Sonia; Friker, Lea; Schaub, Christina; Turiello, Roberta; Sperk, Elena; Mildenberger, Iris; Grau, Franziska; Paech, Daniel; Pietsch, Torsten; Mueller, Wolf; et al.
Abstract: BACKGROUND: We recently reported favorable safety, promising clinical efficacy and immunohistochemical indicators of response after radiotherapy (RT) plus escalating doses of the CXCL12-neutralizing RNA-Spiegelmer olaptesed pegol (NOX-A12) for glioblastoma in the German multicenter phase 1/2 GLORIA trial (NCT04121455). Here, we report outcomes after RT plus dual inhibition of vasculogenesis (NOX-A12) and angiogenesis (bevacizumab). METHODS: After establishing safety in the monotherapy arm, we enrolled six patients with incompletely resected GBM, ECOG ≤ 2, age ≥ 18 and without MGMT promoter hypermethylation into a pre-planned expansion arm. Patients received standard RT (60 Gy in 30 fractions), continuous i.v. infusions of NOX-A12 (600 mg/week) and i.v. infusions of bevacizumab (10 mg/kg q2w). The primary endpoint was safety. Secondary endpoints included radiographic response, perfusion/diffusion imaging and neurologic performance. RESULTS: Dual treatment was well-tolerated and safe. Of all G ≥ 2 AEs (n = 37), two G2 events (5.4%) were deemed related to NOX-A12. There were no dose-limiting toxicities and no treatment-related deaths. Longitudinal NANO assessment revealed stable neurologic functioning in all patients. Five out of six patients achieved partial responses (PRs) as per mRANO in week 9. All PRs remained durable at a median follow up of 5.6 months (range 3.6 to 9.3 months). No progression occurred. The mean best response was -65.9% (-13.3% to -99.9%) for target lesion sums and -92.1% (-76.2% to -100%) for non-target lesion (NTL) sums. In all three patients with NTL at least one lesion disappeared. The mean best change from baseline of the highly perfused-tumor fraction was -84.5% (-51.9% to -100%) and the mean best change of the apparent diffusion coefficient was 20.1% (-24.5% to 59.1%). CONCLUSION: Interim data of the ongoing trial confirm the previously established safety profile of NOX-A12 and suggest improved efficacy of dual inhibition of post-radiogenic angio- and vasculogenesis by the addition of bevacizumab.